Логіка керованості економічної безпеки підприємства - Ляшенко, О. М. (Ways to Improve Construction Efficiency, 2013)
Predicates logic handling of economic security are made. Controllability of economic security is a range of consequences of managerial influence on processes that occur in the system of economic security together. These processes are: reconciling the interests of internal and external stakeholders of the enterprise, address threats to economic security companies and the formation of resources. The overall result of the flow of such processes is to create sufficient conditions for achieving economic freedom of enterprise.